2020
DOI: 10.1111/jog.14397
|View full text |Cite
|
Sign up to set email alerts
|

Levels of serum Hoxb3 and sFlt‐1 in pre‐eclamptic patients and their effects on pregnancy outcomes

Abstract: Aim: We aimed to explore a new approach and theoretical basis for the diagnosis, treatment and prognosis of pre-eclampsia. Methods: In total, 103 pre-eclamptic patients (study group: SG) and 100 healthy pregnant women (control group: CG) were enrolled. Reverse transcription quantitative polymerase chain reaction (RT-qPCR) was used to detect the expression level of serum Hoxb3. Enzyme-linked immunosorbent assay was used to detect the content of serum sFlt-1. Pregnancy outcomes in the two groups were recorded, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…39 While the reduction was subtle, resulting in modest predictive ability, Adm may have clinical utility if combined with other molecules. Evidence that mRNA biomarkers could improve prediction if combined with proteins was demonstrated by Zhou et al 51 A combination of Hoxb3 with sFlt-1 resulted in greater area under the Receiver Operator Curve (ROC) than either biomarker alone, but a major limitation is that samples were collected following diagnosis. Thus, the true predictive capacity of Hoxb3 with sFlt-1 requires validation.…”
Section: Placental Rnasmentioning
confidence: 99%
“…39 While the reduction was subtle, resulting in modest predictive ability, Adm may have clinical utility if combined with other molecules. Evidence that mRNA biomarkers could improve prediction if combined with proteins was demonstrated by Zhou et al 51 A combination of Hoxb3 with sFlt-1 resulted in greater area under the Receiver Operator Curve (ROC) than either biomarker alone, but a major limitation is that samples were collected following diagnosis. Thus, the true predictive capacity of Hoxb3 with sFlt-1 requires validation.…”
Section: Placental Rnasmentioning
confidence: 99%
“…The development and growth of the fetus are determined by the exchange of nutrients through the placenta during pregnancy. HoxB3 is a major regulator of angiogenesis [ 19 ], which makes us speculate that HoxB3 may impact placental status and, therefore, fetal growth, too.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a decrease of HoxB3 might inhibit the invasion of trophoblast cells [ 6 ]. HoxB3 has a certain significance for the risk evaluation of pre-eclampsia [ 19 ]. HoxB3 promotes invasive behaviour of endothelial cells in response to angiogenic stimulation [ 1 ] and is required for the morphogenesis of new capillary tubes [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…[35] In pregnancy hypertensive disorder patients, studies showed a significant increase in miRNA-1233 expression that suppresses the expression levels of HoxB3-major regulator of angiogenesis-which leads to proliferation and trophoblast cells invasion decrease in placental tissue from pregnancy hypertensive disorder patient. [35,36] Another three preeclampsia rodent model studies show elevated miR-210 in part driven by HIF-1α and NF-κBp50, induced by hypoxia and/or immune-mediated processes may contribute in preeclampsia by inhibiting anti-inflammatory Th2-cytokines. [37] miRNA125b as Biomarker Third Trimester of Pregnancy Hypertensive Disorder miR-125b in pregnant women can be detected from several different sites, the plasma from the mother, where it is often called the maternal circulating miR-125b and the placental cells, where it is called as placental miR-125b.…”
Section: Methodsmentioning
confidence: 99%